Toot and Puddle - Holly Hobbie (New York, United States Little, Brown & Company, 1997)
When Puddle wakes up one morning, Toot is missing! Although Puddle usually prefers to stay home in Woodcock Pocket, his concern for his best friend prompts him to set off. Puddle takes a train and then a plane, and eventually finds himself in a far-away place. And who do you think he finds? Holly Hobbie's story of a friendship that extends to the top of the world will be welcomed by the many fans of Toot and Puddle.
Keywords: Read Aloud -- Read Aloud